The Effects of Logo Shape, Logo Color, Typography and Service Quality Towards Brand Image on PT. Gojek Indonesia - Shafira Azzahira; I Made Bayu Dirgantara (Journal of Economics and Business, 2021)
This research aims to explain the influences of logo shape, logo color, typography and service quality towards brand image on PT. Gojek Indonesia. There are four independent variables, those are logo shape. Logo color, typography and service quality that researcher wanted to know how much those variables influence on the image of Gojek as a dependent variable. This research used a non-probability sampling technique with a purposive sampling method. The population of the research as a media. The samples in this research were 115 respondents. This research examines the hypothesis by using Statistical Package for Social Sciences (SPSS). The results of this study indicate that typography and service quality have a positive and significant effect on brand image. Meanwhile, logo shape and logo color does not have a significant effect on brand image. Service quality as a dominant variables that influence the brand image.